The effect of coating of chitosan incorporating and green tea extract on shelf life of walnut kernel - Moslem Sabaghi; Yahya Maghsoudlou; Morteza Khomeiri; Aman Mohammad Ziaiifar (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2015)
The effects of coating from chitosan incorporating green tea extract on lipid oxidation, fungal growth and sensory properties of walnut kernel were studied. The green tea extract obtained from green tea (GT) and chitosan (C) powder were combined to obtain the final concentrations of C-GT: 5-0, 5-5, 5-10, 10-0, 10-5 and 10-10 gram per liter in aqueous coating solution. Effective inhibition of lipid oxidation and fungal growth during storage of walnut kernel (18 weeks) was possible through Chi10 coating combined with GT. Different proportions of GT had no significant effect (P<0.05) on lipid oxidation. Regarding the C10 with different proportions of GT, fungal growth was not detected during storage period. Throughout the storage, coating without GT showed no significant (P<0.05) effect on sensory properties, however Chi10-GT10, was significantly (P<0.05) unacceptable by the  panelists. The results suggested that Chi10-GT5 could prolong the shelf life of walnut kernel.